PENGARUH VARIASI MENU, HARGA, DAN PROMOSI MELALUI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN BOMBOLONI (Studi di Virous Bombolone & Donuts Sidoarjo) - Firdaus, Jessica Elizabeth; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
This study aims to analyze and explain the influence of menu variations, prices, and promotions through Instagram on the purchase decision of bomboloni consumers at Virous Bombolone & Donuts Sidoarjo. The research method used is a quantitative method. This research was conducted on Jalan Pecantingan No. 70, Sekardangan, Sidoarjo. The subjects in this study were consumers who had bought bomboloni at Virous Bombolone & Donuts Sidoarjo with a total of 100 respondents. The data collection techniques used are questionnaires and interviews. This study uses a classical assumption test which is then tested using a multiple linear regression test. The results of this study show that simultaneously, there is a significant influence of menu variations, prices, and promotions on the purchase decision of bomboloni consumers at Virous Bombolone & Donuts Sidoarjo. However, partially, there was no significant influence of menu variations on the purchase decision of bomboloni consumers at Virous Bombolone & Donuts Sidoarjo, while for the price and promotion variables of each of these variables, the results were obtained that there was a partial significant influence of price and promotion through Instagram on the purchase decision of bomboloni consumers at Virous Bombolone & Donuts Sidoarjo. So from the results of the research, Virous Bombolone & Donuts Sidoarjo needs to build a better communication relationship with consumers and provide stimulus to consumers to increase bomboloni purchase decisions at Virous Bombolone & Donuts Sidoarjo by providing a good impression or experience for consumers.